Konsep Mandheg dalam Karawitan Gaya Surakarta - Ananto Sabdo Aji (Institut Seni Indonesia Yogyakarta, 2019)
Tulisan ini mengungkap mandheg sebagai salah satu konsep lokal di dalam karawitan Jawa gaya Surakarta. Penelitian ini bertujuan untuk menggali persoalan yang terkait dengan pengertian mandheg, proses terjadinya mandheg, hal-hal yang berhubungan dengan pemaknaan, elemen pembentuk, dan fungsi mandheg di dalam proses penggarapan gending. Data dikumpulkan melalui studi pustaka, wawancara, dan pengamatan pertunjukan. Analisis dilakukan dengan menafsirkan kembali pemikiran dan pengalaman pengrawit yang diperoleh melalui realitas pragmatik. Berdasarkan penelitian disimpulkan bahwa mandheg dimaknai sebagai sajian gending yang berhenti sejenak pada sebuah titik dengan ciri pola kendangan mandheg dan alur yang spesifik setelah mandheg. Mandheg dibagi menjadi dua yaitu mandheg kedah dan mandheg pasrèn, dengan elemen pembentuk, antara lain andhegan gawan, kalimat lagu, variabel melodi balungan, dan sekar. Mandheg bersifat wajib dan fakultatif. Andhegan dan variabel yang spesifik membuat mandheg sebagai pembentuk sajian gending menjadi dinamis. The Concept of Mandheg in Karawitan of Surakarta Style. This research reveals mandheg as one of the local concepts of Javanese music, especially the Surakarta style. Generally, some issues are explored in this research are related to the definition of mandheg and the process of mandheg itself. In more depth, this paper also discusses some point relating to the meaning, forming elements, and functions of mandheg in the process of gending work. These points are explained based on data on the presentation of a musical instrument as a factual data exploration media. The data collection was carried out by literature study, interviews, and also as a participant-observer. The analysis is carried out by reinterpreting the thoughts and experience of the pengrawit through practical reality. The interpretation uses the interpretation method and garap analysis. The explanation and getting conclusions are carried out by the inductive method. The mandheg is interpreted as a gendhing presentation that pauses at a point with the characteristic of the pattern of the kendhangan and the spesific flow after mandheg. The mandheg is divided into two, namely the mandheg kedah and mandheg pasrèn, with the elements of forming andhegan gawan, song sentences, balungan melodic variables, and sekar. The tend of mandheg are mandatory and facultative. Andhegan and specific variables make mandheg as forming a dynamic presentationKeyword: mandheg; javanese gamelan; pasrèn